Ultrafast high-temperature sintering (UHS) of Li1.3Al0.3Ti1.7(PO4)3. Issue 15 (1st August 2021) - Lin, Yong; Luo, Nan; Quattrocchi, Emanuele; Ciucci, Francesco; Wu, Jinghua; Kermani, Milad; Dong, Jian; Hu, Chunfeng; Grasso, Salvatore
Abstract: Li1.3 Al0.3 Ti1.7 (PO4 )3 (LATP) is one of the most promising inorganic solid electrolytes, it combines together good electrochemical stability with high ionic conductivity. Its properties are strongly dependent on the consolidation route and the relevant literature confirms the beneficial role of rapid heating. Therefore, the recently emerged Ultrafast High-temperature Sintering (UHS) was selected to prevent undesired Li loss during processing. UHS densified LATP up a relative density of 90.2% within 100s while achieving a ionic conductivity as high as 4.7 × 10 −4 S/cm at 25 °C. The rapid UHS heating (≈1500 °C/min) justified the increased density and slightly improved ionic conductivity of 4.67 × 10 −4 S/cm if compared to counterparts (i.e., 85.4% and 3.9 × 10 −4 S/cm) produced using conventional sintering at 900 °C with a dwell time of 6 h. Additionally, the UHSed electrolyte resulted in a 20% increase in grain boundary conductivity compared to conventionally sintered bulks. We identified a narrow processing window (discharge duration of 100 s and current of 20 A) suitable for producing dense and decomposition free LATP electrolytes.